(untitled) (Perner’s Contacts, 2009)
This article deals with the demand for public transportation of people with disabilities (wheelchairs) and factor important for this people in decision-taking. There are important factors of this process described. Demand for public transportation of (not only) wheelchairs is depend on accessibility of all subsystems of public transportation and on needful information availability.